2010
DOI: 10.1002/pen.21662
|View full text |Cite
|
Sign up to set email alerts
|

Optical monitoring of the injection molding of intercalated polypropylene nanocomposites

Abstract: Intercalated polypropylene (PP)/clay nanocomposites were produced by twin screw extrusion; afterwards, the optical monitoring of their injection molding was done using a laser sensor. The transmitted light intensity as a function of molding time was measured. The mold and melt temperatures, packing pressure and flow rate were changed. The nanocomposite had higher induction times than the PP, that is, scattering structures were detected later in the nanocomposite than in the PP, which was attributed to a retard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…The thickness of the skin of all of the samples was measured, and it is shown in Table ; we observed that, as expected, the lower Q was, the lower the shear rate and the higher the time for the beginning of the flow‐induced crystallization to occur were, as confirmed by other works . Therefore, the thickness of the frozen skin layer was higher.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The thickness of the skin of all of the samples was measured, and it is shown in Table ; we observed that, as expected, the lower Q was, the lower the shear rate and the higher the time for the beginning of the flow‐induced crystallization to occur were, as confirmed by other works . Therefore, the thickness of the frozen skin layer was higher.…”
Section: Resultssupporting
confidence: 78%
“…All of the samples also showed cold crystallization, even the thermally treated ones; this indicated that the thermal treatment was not enough to attain the highest amount of crystallinity in the samples. The addition of HA slightly increased the amount of crystallinity of the thermally and non thermally treated samples; this was in contrast to other results . The amount of crystallinity was also dependent of the injection‐molding conditions, as expected; for example, PEEK and the nanocomposite injected under condition 1 (lowest Q ) had the lowest X c _DSC because a low Q favored the formation of a thicker skin (frozen layer) and a low X c _DSC .…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…As concentrações finais dessas soluções estão descritas na Tabela 1. uma escala competitiva com outros materiais convencionais. A nanoargila montmorilonita vem sendo fonte de constantes estudos de intercalação química e esfoliação, pois possui origem natural e vantagens como boas capacidade de delaminação, alta resistência a solventes, estabilidade térmica para suportar os processos de transformação e elevada razão de aspecto [1,[5][6][7][8][9][10][11][12] . Nanofibras de nanocompósitos obtidas pelo processo de eletrofiação e com propriedades especiais têm sido amplamente apresentadas na literatura recente [13][14][15][16][17][18][19] .…”
Section: Via Mistura No Estado Fundidounclassified
“…With respect to the structure that nanocomposites develop, Moretti et al [49] observed that intercalated PP/clay nanocomposites produced by twin-screw extrusion showed a second core, a thicker skin layer, highly oriented nanoclay's tactoids in the skin region, and average spherulite size smaller than PP. They also noted that the neat PP sample had average spherulite size larger than the nanocomposite samples.…”
Section: Morphology Developmentmentioning
confidence: 99%